Folate deficiency in patients with classical galactosemia: A novel finding that needs to be considered for dietary treatments - Muhittin Çelik; Nezir Özgün; Osman Akdeniz; Mücahit Fidan; Heybet Tüzün; Mehmet Şah İpek; Merve Emecan; Fatma Tuba Eminoğlu (The Turkish Journal of Pediatrics)
The objectives of the study were to assess folate deficiency in patients with classic galactosemia, and to determine whether folic acid supplementation has an effect on galactose-1-phosphate uridyltransferase enzyme activity. Sixty-one newborn infants diagnosed with classic galactosemia between 2010 and 2017 were retrospectively evaluated. Within this group, 48 patients with Q188R homozygous mutation alone were enrolled into the study. Serum folate concentration was studied using chemiluminescence; and in folate deficient patients, galactose-1-phosphate uridyltransferase measurements before and after folic acid supplementation (100 mg/day folic acid for 30 days) were performed using an enzymatic calorimetric measurement technique based on kinetics. The serum folate level was low ( < 4 ng/ml) in 12 patients (25%). The galactose-1-phosphate uridyltransferase enzyme activity after folic acid supplementation was significantly higher than the values before folic acid supplementation (1.00±0.19 U/g Hb vs. 0.74±0.23 U/g Hb, p < 0.05); but was still less than the normal levels. Folate deficiency, most likely due to poor dietary intake, may develop in pediatric patients with classical galactosemia, and folic acid should be supplemented. Folic acid supplementation appears to have a low, but statistically significant, effect on galactose-1-phosphate uridyltransferase enzyme activity, but comprehensive research is needed to clarify whether there is any clinical significance.